Case Report: Subacute combined degeneration of the spinal cord mimic accompanying adaptor protein-3B2-IgG - Liu, Ying; Gao, Guo-Hui; Lin, Jie; Sun, Chong; Zhao, Yan-Yin (Frontiers in Immunology, 2025)
We here report the first case of subacute combined degeneration (SCD)-mimic accompanying adaptor protein-3B2 (AP3B2) antibody, expanding the clinical spectrum of AP3B2 antibody-associated disorders. A 55-year-old woman presented with progressive limb numbness, gait instability, and sensory ataxia over six years, unresponsive to prolonged vitamin B12 therapy. Neurological examination revealed combined posterior column, lateral column, and peripheral nerve involvement. Cervical spinal MRI demonstrated posterior column hyperintensity, while electrophysiology confirmed sensory-predominant peripheral neuropathy. Anti-AP3B2 antibodies were detected in serum (titer 1:100), with no evidence of vitamin B12 malabsorption, copper deficiency, paraneoplastic syndromes, or other immune abnormalities. Clinically resembling SCD, key discrepancies included: initial mononeuropathy multiplex/sensory neuronopathy evolving into symmetric polyneuropathy; normal vitamin B12 metabolism despite treatment resistance; absence of megaloblastic anemia. Based on AP3B2 expression in dorsal root ganglia, spinal cord, and cerebral cortex, we propose the novel entity “anti-AP3B2 antibody-associated SCD-mimic phenotype,” highlighting its distinction from classical SCD. AP3B2 antibodies likely mediate neuronal injury via CD8+ T-cell cytotoxicity, consistent with intracellular antigen-targeting autoimmune mechanisms. While prior AP3B2-associated cases primarily featured cerebellar ataxia or sensory ataxia, this case uniquely manifests the SCD-like triad (posterior column, pyramidal tract, and peripheral nerve damage). Clinicians should consider anti-AP3B2 antibody screening in SCD-like patients refractory to vitamin B12 therapy. Although immunotherapy responses remain limited in reported cases, early identification may optimize diagnostic and therapeutic strategies.